The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00421-011-2024-y
|View full text |Cite
|
Sign up to set email alerts
|

No case of exercise-associated hyponatraemia in top male ultra-endurance cyclists: the ‘Swiss Cycling Marathon’

Abstract: The prevalence of exercise-associated hyponatraemia (EAH) has been investigated in endurance athletes such as runners and Ironman triathletes, but not in ultra-endurance road cyclists. We assessed fluid intake and changes in body mass, urine specific gravity and plasma sodium concentration ([Na(+)]) in 65 ultra-endurance road cyclists in a 720-km ultra-cycling marathon, the 'Swiss Cycling Marathon'. The cyclists lost 1.5 (1.7)% body mass (P < 0.01). No athlete developed EAH. Fluid intake was associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 50 publications
2
36
1
Order By: Relevance
“…The reported incidence of asymptomatic EAH has ranged from 0%30 53 to 51%54 immediately post-race. In a study of an ultramarathon, 67% of the participants were hyponatraemic (asymptomatic) at some point during the race, but only 27% finished the race with serum [Na + ] <135 mmol/L (40% self-corrected prior to finishing the event) 11.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reported incidence of asymptomatic EAH has ranged from 0%30 53 to 51%54 immediately post-race. In a study of an ultramarathon, 67% of the participants were hyponatraemic (asymptomatic) at some point during the race, but only 27% finished the race with serum [Na + ] <135 mmol/L (40% self-corrected prior to finishing the event) 11.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of asymptomatic EAH in Ironman triathlons in different environments has been reported to range from negligible,10 to as high as 18%57 and 25% 19. In studies on endurance cyclists, the incidence of asymptomatic EAH has ranged from 0% in a 720 km race,30 to 12% in a 109 km race 15. In a 26.4 km swim, 17% of swimmers developed asymptomatic hyponatraemia 32.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported slightly higher fluid intake (530 to 670 ml/hr), but also no increased incidence of dehydration based on plasma volume changes and USG during other ultra-endurance events (Neumayr et al, 2003(Neumayr et al, , 2005Rüst et al, 2012).…”
Section: Fluid Intake and Hydration Statusmentioning
confidence: 94%